Estudio y análisis de la estrategia publicitaria de la campaña Dove Legacy 2014 - Sánchez Sánchez, Aggie Melissa (2019)
The present work deals with the advertising strategies employed in the Dove Legacy campaign in 2014. After an experiment executed to mothers and daughters, it results that women do not feel good about their physical appearance, generating serious self-esteem problems. In this project it is also possible to appreciate the importance and role of marketing in advertising. Studying the weaknesses of its consumers and applying strategies to meet their needs, as well as taking advantage of their strengths and opportunities to compete with other companies. Analysis techniques were applied, studying the advertising strategies of the Dove personal hygiene products company. Concluding that Dove knows how to connect with its market, managing precise strategies for its consumers, satisfying their needs. Resulting beneficiaries of this study are people looking for a source of information, be it on the subject of marketing and advertising, their strategies, the empowerment of women and the Dove line.